2020
DOI: 10.1016/j.semcdb.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein interactions of human viruses

Abstract: Viruses infect their human hosts by a series of interactions between viral and host proteins, indicating that detailed knowledge of such virus-host interaction interfaces are critical for our understanding of viral infection mechanisms, disease etiology and the development of new drugs. In this review, we primarily survey human host-virus interaction data that are available from public databases following the standardized PSI-MS format. Notably, available host-virus protein interaction information is strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 107 publications
0
30
0
Order By: Relevance
“…Studying virus-host protein–protein interactions is an important strategy to better understand the functions of viral proteins [ 31 , 32 ]. Regarding paramyxovirus M protein and host protein interactions, it has been reported that the interaction of the Nipah and Hendra virus M proteins with AP3B1 protein promotes virus-like particle (VLP) production [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studying virus-host protein–protein interactions is an important strategy to better understand the functions of viral proteins [ 31 , 32 ]. Regarding paramyxovirus M protein and host protein interactions, it has been reported that the interaction of the Nipah and Hendra virus M proteins with AP3B1 protein promotes virus-like particle (VLP) production [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protein-protein interactions, either transient or as part of stable complexes, are key to most cellular processes and biological pathways. In recent years, it has in fact become clear that a detailed description of specific protein interaction networks is required for our understanding of many disease states and the development of new drugs (Goodacre et al, 2018;Laddach et al, 2018). Accordingly, experimental approaches dedicated to the identification of proteinprotein interactions are fundamental to understanding complex biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the researchers have little knowledge of the molecular biology of SARS-CoV2 infection [16]. In the present state of art, viral infection mechanism is not fully understood though various proteinprotein interactions (PPIs) of virus and host are known [17,18]. So identifying interactions between the SARS-CoV2 virus proteins and host proteins helps understand the mechanism of viral infection and develop treatments and vaccines [19].…”
Section: Introductionmentioning
confidence: 99%